2021
DOI: 10.1111/os.12959
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Collapse Prevented Following Teriparatide Treatment in Postmenopausal Kümmell's Disease Patients with Severe Osteoporosis

Abstract: Objective: To compare the preventive effects of teriparatide and alendronate on the progression of vertebral body collapse in postmenopausal single-level Kümmell's disease (KD). Methods: From March 2013 to December 2020, the medical records for 53 postmenopausal single-level KD patients who received conservative treatment with teriparatide (25 patients, teriparatide group) or alendronate (28 patients, alendronate group) were retrospectively reviewed. Midsagittal computed tomography (CT) images were analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…A surgeon’s main activity is to perform surgery and care. However, a big number of publications in the years 2017 to 2020 were related to alternative methods for managing orthopaedic conditions, medical treatments, infiltrations, physical therapy, patient education, diet, and so many others [ 4 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A surgeon’s main activity is to perform surgery and care. However, a big number of publications in the years 2017 to 2020 were related to alternative methods for managing orthopaedic conditions, medical treatments, infiltrations, physical therapy, patient education, diet, and so many others [ 4 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It could reduce the risk of fracture through promoting bone formation 26–28 . In addition, for PMOP patients with Kümmell's disease, PTH could prevent progressive vertebral collapse 29 . Recently, Li et al .…”
Section: Introductionmentioning
confidence: 99%
“… 26 , 27 , 28 In addition, for PMOP patients with Kümmell's disease, PTH could prevent progressive vertebral collapse. 29 Recently, Li et al . found that PTH could increase bone mass in conventionally housed mice.…”
Section: Introductionmentioning
confidence: 99%
“…The anabolic effect mediated by PTH can be beneficial in implantation fusion and fracture healing ( Swarthout et al, 2002 ). Moreover, PTH may reduce the risk of osteonecrosis (e.g., Kummell’s disease) ( Keskinruzgar et al, 2016 ; Gou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%